The Effects of Cooperative versus Competitive Word Games on EFL Learners` Vocabulary Gain, Motivation, and Class Atmosphere - Fotovatnia, Zahra; Namjoo, Maryam (Richtmann Publishing, 2013)
English vocabulary is considered difficult to learn and use in real life situations by most Iranian learners. In addition, many ofthem feel bored in vocabulary classes since they do not have the opportunity to take part in learning process, therefore, theylack necessary motivation to be pushed forward. Besides, they have not changed their learning habits, such as writing wordson paper, trying to learn by heart or learning passively through teachers` explanations. The reason must be that the maintechniques used to practice in memorization while the features like fun, motivation and effort are ignored in almost all Englishclasses. To help learners find language classes, especially vocabulary lessons more interesting, and to achieve more, theresearcher used word games, which are generally engaged as a source of entertainment to serve an educational purpose, asinstructional tools in practicing newly taught words. Moreover, the researcher compared the effects of two types of word games(cooperative versus competitive) on learners` motivation, attitudes toward their teacher, class atmosphere, and vocabularyachievement, in order to investigate which game type was more successful in this field. In order to achieve this goal, this studyhas been done on 60 male English learners with the age range of 17-19 years old. Among these learners, 40 were consideredas the experimental (in 2 different experimental groups), and the other 20 learners as the control. To gather data, theseinstruments have been used: a motivation questionnaire, a questionnaire about word games, a classroom atmospherequestionnaire, vocabulary tests, and teacher`s interview. Besides, 2 different categories of word games (cooperative versuscompetitive games) were used in this study to compare their effects on EFL vocabulary learning. The results show that bothtypes of word games affect learners` vocabulary learning, increase their motivation, change their attitudes toward their teacher,and also create a positive atmosphere in their classroom. Moreover, through comparing effects of these games, the researcherfound out that for some learners, cooperative word games could affect their vocabulary learning by increasing their motivationand providing a positive atmosphere in their classroom, while for some others, competitive word games were more effective.Consequently, it cannot be stated exactly which type of these games were more successful in this study. Curriculum designers,English textbook authors, and those who train EFL teachers can use these findings and improve English education andlearning in words in English classes in Iran. It other words, it is suggested to use word games in English classes to increaselearners` motivation, vocabulary learning, and also to provide a more positive atmosphere in the classroom.